2005
DOI: 10.1586/14787210.3.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chancroid in resource-poor countries

Abstract: Chancroid, formerly a major cause of the genital ulcer disease syndrome, remains an important cofactor in both the transmission and acquisition of HIV-1 infection. Those countries with the greatest burden of HIV also have some of the highest prevalence rates of chancroid worldwide. The diagnosis of chancroid, caused by the fastidious bacterium Haemophilus ducreyi, is both expensive and difficult in many resource-poor areas. These areas of the world use syndromic management to treat genital ulcers and such an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Haemophilus ducreyi , the causative agent of the sexually transmitted disease chancroid, is a gram-negative obligate human pathogen [ 1 , 2 ]. Chancroidal infection has been shown to facilitate the transmission and acquisition of HIV [ 3 ]. Recent studies have demonstrated that H .…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilus ducreyi , the causative agent of the sexually transmitted disease chancroid, is a gram-negative obligate human pathogen [ 1 , 2 ]. Chancroidal infection has been shown to facilitate the transmission and acquisition of HIV [ 3 ]. Recent studies have demonstrated that H .…”
Section: Introductionmentioning
confidence: 99%
“…Although chancroid is currently considered rare in the United States (http: //www.cdc.gov/std/stats08/other.htm), outbreaks of H. ducreyi infection occurred in large American cities throughout the 1980s and 1990s (10,25). During these times, chancroid was endemic in sub-Saharan Africa, Asia, and the Caribbean (6,44). It is difficult to assess the current epidemiology of chancroid because of syndromic management of GUDs and a lack of reporting and diagnostic tools.…”
mentioning
confidence: 99%
“…Haemophilus ducreyi is the causative agent of chancroid, a genital ulcer disease that facilitates both the transmission and acquisition of HIV-1 (4,45). An obligate human pathogen, H. ducreyi infects epithelial surfaces and primarily remains localized in the skin (49).…”
mentioning
confidence: 99%